Upaya Meningkatkan Kemampuan Motorik Kasar Melalui Pembelajaran Senam Fantasi di Taman Kanak-Kanak Darul Yaqin Koto Ranah - Amira Amira; Mohammad Fauziddin; Musnar Indra (LPPI Yayasan Almahmudi bin Dahlan, 2023)
This study aims to improve the gross motor skills of children aged 4-5 years through rhythmic gymnastics at TK Darul Yaqin Koto Ranah village, District Kabun, Rokan Hulu Regency. The type of research is Classroom Action Research which is carried out collaboratively between researchers and classroom teachers. This research consisted of two cycles and each cycle was conducted in two meetings. The subjects of this study were 10 children of the Darul Yaqin Kindergarten Playgroup in Koto Ranah Village, Kabun District, which consisted of 5 boys and 5 girls. Data collection techniques through observation and documentation. The instruments used in this study were observation sheets and documentation. Techniques Data analysis was carried out in a qualitative descriptive manner. The results showed that there was an increase in gross motor skills after using rhythmic gymnastics. The child's gross motoric improvement every cycle experiences development. This is evidenced from the results of research 7 out of 10 children or 70% of the total have been able to do rhythmic gymnastics and begin to proficiently move their bodies without the help of their teachers. Keywords: Ability, gross motor skills, rhythmic gymnastics